2016
DOI: 10.1109/tpel.2015.2444386
|View full text |Cite
|
Sign up to set email alerts
|

DC-Link Voltage Coordinated-Proportional Control for Cascaded Converter With Zero Steady-State Error and Reduced System Type

Abstract: Abstract-Cascaded converter is formed by connecting two subconverters together, sharing a common intermediate DC-link voltage. Regulation of this DC-link voltage is frequently realized with a Proportional-Integral (PI) controller, whose high gain at DC helps to force a zero steady-state tracking error. Such precise tracking is however at the expense of increasing the system type, caused by the extra pole at the origin introduced by the PI controller. The overall system may hence be tougher to control. To reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The control block diagram using the feedforward control is shown in Figure 4. Since the full-bridge inverter works at the line frequency, the full-bridge inverter can be equivalent to a load (R load ), given in (9). The transfer function of the compensator is shown in (10).…”
Section: Stability Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The control block diagram using the feedforward control is shown in Figure 4. Since the full-bridge inverter works at the line frequency, the full-bridge inverter can be equivalent to a load (R load ), given in (9). The transfer function of the compensator is shown in (10).…”
Section: Stability Analysismentioning
confidence: 99%
“…7,8 However, the output voltage accuracy is low with the PI control, so the loads that require high voltage accuracy cannot be powered. 9 Therefore, the proportional resonance (PR) control was proposed to improve the output voltage accuracy. 10 The system gain can be infinitely amplified by using the PR control at a constant frequency, so the output voltage accuracy is high at a specific frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation outcomes clearly showed that the linearized system neatly illustrates the nonlinear system round the same working conditions and PI controllers realize desired performance and robustness. In (Tian, Loh, Deng, Chen, & Hu, 2016), the PI controller achieved the modification of dc-link voltage. A significant improvement in dc helps to make the tracking error stable.…”
Section: 1introductionmentioning
confidence: 99%
“…In spite of various converters available, Dual Active Bridge (DAB) converter is mostly preferred converter for integrating EV to the grid. DAB is mainly preferred because of its bidirectional power flow, with symmetrical structure, soft switching and high-power density [3], [4]. So, this converter is preferred for cascading with an inverter.…”
Section: Introductionmentioning
confidence: 99%